2019
DOI: 10.18203/2349-3291.ijcp20192767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin A supplementation on preventing recurrent acute lower respiratory tract infections in children

Abstract: Background: Acute Lower Respiratory Tract Infections (ALRTI) remains the major cause of increased morbidity and mortality in under-five children. Vitamin A has a protective role against infections in children. Vitamin A supplementation is given to under-five children as part of the National Immunization Programme in India. The aim of this study was to find out the effectiveness of vitamin A supplementation in preventing the recurrent ALRTI (≥3 episodes per year) in under-five children.Methods: A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[10] According to Murthy et al reported that children who received vitamin A supplementation had a significantly lower incidence of recurrent acute lower respiratory tract infections than those who did not receive vitamin A supplementation (P 0.001). [12] A significant association between vitamin A deficiency and RRTI, as well as the severity of disease development observed by this study, can be explained by the fact that micronutrient deficiencies, such as a of vitamins and minerals, are associated with a variety of medical conditions, including an increased risk of developing upper and lower RTIs. [23] Vitamin A deficiency alters the respiratory epithelium and impairs humoral as well as cellular immunity.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[10] According to Murthy et al reported that children who received vitamin A supplementation had a significantly lower incidence of recurrent acute lower respiratory tract infections than those who did not receive vitamin A supplementation (P 0.001). [12] A significant association between vitamin A deficiency and RRTI, as well as the severity of disease development observed by this study, can be explained by the fact that micronutrient deficiencies, such as a of vitamins and minerals, are associated with a variety of medical conditions, including an increased risk of developing upper and lower RTIs. [23] Vitamin A deficiency alters the respiratory epithelium and impairs humoral as well as cellular immunity.…”
Section: Discussionmentioning
confidence: 57%
“…[ 10 ] According to Murthy et al reported that children who received vitamin A supplementation had a significantly lower incidence of recurrent acute lower respiratory tract infections than those who did not receive vitamin A supplementation (P 0.001). [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation